2,4-dichlorophenoxyacetic acid-induced oxidative stress: Metabolome and membrane modifications in Umbelopsis isabellina, a herbicide degrader. - Przemysław Bernat; Justyna Nykiel-Szymańska; Paulina Stolarek; Mirosława Słaba; Rafał Szewczyk; Sylwia Różalska (PLoS ONE)
The study reports the response to herbicide of the 2,4-dichlorophenoxyacetic acid (2,4-D)-degrading fungal strain Umbelopsis isabellina. A comparative analysis covered 41 free amino acids as well as 140 lipid species of fatty acids, phospholipids, acylglycerols, sphingolipids, and sterols. 2,4-D presence led to a decrease in fungal catalase activity, associated with a higher amount of thiobarbituric acid-reactive substances (TBARS). Damage to cells treated with the herbicide resulted in increased membrane permeability and decreased membrane fluidity. Detailed lipidomic profiling showed changes in the fatty acids composition such as an increase in the level of linoleic acid (C18:2). Moreover, an increase in the phosphatidylethanolamine/phosphatidylcholine ratio was observed. Analysis of fungal lipid profiles revealed that the presence of 2,4-D was accompanied by the accumulation of triacylglycerols, a decrease in ergosterol content, and a considerable rise in the level of sphingolipid ceramides. In the exponential phase of growth, increased levels of leucine, glycine, serine, asparagine, and hydroxyproline were found. The results obtained in our study confirmed that in the cultures of U. isabellina oxidative stress was caused by 2,4-D. The herbicide itself forced changes not only to membrane lipids but also to neutral lipids and amino acids, as the difference of tested compounds profiles between 2,4-D-containing and control samples was consequently lower as the pesticide degradation progressed. The presented findings may have a significant impact on the basic understanding of 2,4-D biodegradation and may be applied for process optimization on metabolomic and lipidomic levels.